Two Kenya Countries advancing Kenya’s third National Climate Change Action Plan Goals - Sagliocco, Livia; Kenduiywo, Benson; Pacillo, Grazia (2025)
In 2024, researchers from the Alliance Bioversity-CIAT, contributing to the CGIAR Research Initiative on Climate Resilience (ClimBeR), supported Laikipia and Turkana counties in advancing climate resilience and peace through Climate-Smart Agriculture (CSA). The establishment of county-level Climate-Smart Agriculture Multi-Stakeholder Platforms (CSA-MSP) and a piloted training course increased the capacity of officials, NGOs, and farmers to begin integrating CSA practices, addressing resource-based conflicts, and promoting adaptation strategies, as part of the actions agreed in the Adaptation Technical Analysis Report (ATAR).